(untitled) (Південний архів (історичні науки), 2021)
The purpose of the work. The south of modern Ukraine has always been geographically and historically particularly interesting for researchers. Its geographical indicators make it possible to analyze theories of the origin of man, development, formation of human society under the influence of climatic conditions to its highest degree - its own independent state. The Soviet state’s rather popular concepts, designed to artificially unite and forcibly bring peoples together in tsarist Russia, have not withstood the test of time and history. The use of the concept of the South Ukrainian region requires a definition: we move freely through the territory of modern Kherson, Odessa, Mykolaiv, Zaporizhia regions and the Autonomous Republic of Crimea. Results and scientific novelty of the study According to the chronology, scientists use the names Little Russia, New Russia, contained in primary sources, archival documents, memoirs, correspondence. The presence of the French component in the culture, history, mentality of the population of the region give grounds for reflections on demographic data. A relatively small number of representatives of France have influenced the culture, economy, domestic policy, self-identification of the inhabitants of our region. Accordingly, the German colony, the Swedish village, the Bulgarian, Greek settlements in the history of the region are present and studied, as for the French - there are no such clear characteristics.